Endocrine Conditions and COVID-19 - Shekhar, Skand; Wurth, Rachel; Kamilaris, Crystal D. C.; Eisenhofer, Graeme; Barrera, Francisco J.; Hajdenberg, Michelle; Tonleu, Joselyne; Hall, Janet E.; Schiffrin, Ernesto L.; Porter, Forbes; Stratakis, Constantine A.; Hannah-Shmouni, Fady (Hormone and Metabolic Research, 2020)
COVID-19 was declared a global pandemic by the WHO and has affected millions of patients around the world. COVID-19 disproportionately affects persons with endocrine conditions, thus putting them at an increased risk for severe disease. We discuss the mechanisms that place persons with endocrine conditions at an additional risk for severe COVID-19 and review the evidence. We also suggest precautions and management of endocrine conditions in the setting of global curfews being imposed and offer practical tips for uninterrupted endocrine care.
Keywords: COVID-19; endocrinology; diabetes; hypertension; obesity; metabolic syndrome